Prensa musical en línea. El impacto de las suscripciones digitales y los muros de pago en la cobertura periodística sobre música: el caso Rockdelux (2020-2021) - Alayo Orbegozo, Fernando (2023)
In recent years, the music press has resorted to digital content to survive in the Internet era. It is the case of the Spanish magazine Rockdelux, which in 2020 closed its print edition to become an online platform with digital subscriptions. The objective of this research is to define the characteristics of the journalistic coverage developed by this media in its renewed website Rockdelux.com. For this purpose, this study analyzed more than 1,300 articles published during the transition from paper edition to digital edition; through an own methodology developed to compare editorial preferences on specific musical and journalistic genres. The conclusion was that the new Rockdelux with paywall has prioritized writing articles on trending music, such as reggaeton and hip hop —in addition to having increased the publication of short and immediate texts, such as reviews and news.